Caio Prado Jr. and the meaning of colonization: the inheritance of the brazilian delay to the revolutionary fight - Alcantara, Rafael dos Santos; Alcantara, Rodrigo dos Santos (Faculdade de Ciências e Letras - Unesp - Araraquara., 2019)
This article intend to investigate how Caio Prado Jr. puts the question regarding the meaning of the colonization of Brazil, exposing their particularities and, from that, how this process implied on the configuration of the revolutionary struggle of the left in Brazil. Therefore, will be exposed the criticism of Caio Prado Jr. to the dominant thinking about pre-capitalism in Brazil and which are the implications of this theory in the revolutionary political action.